2019
DOI: 10.4103/ccd.ccd_810_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Indigenously Developed Nano-Hydroxyapatite Crystals from Chicken Egg Shell on the Surface Hardness of Bleached Human Enamel

Abstract: Objective: The objective was to evaluate the effect of nano-hydroxyapatite (nHA) derived from chicken eggshell on bleached human enamel in comparison with commercial casein phophopeptide-amorphous calcium phosphate (CPP-ACP) paste using Vickers microhardness test. Materials and Methods: nHA powder was prepared from chicken eggshell using combustion method. nHA slurry was prepared by mixing 1.8 g of nHA powder with 0.3 ml of distilled water. Forty intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Kunam et al . [ 25 ] supported our findings. They reported that nHA showed a significant elevation on the surface enamel microhardness.…”
Section: Discussionsupporting
confidence: 91%
“…Kunam et al . [ 25 ] supported our findings. They reported that nHA showed a significant elevation on the surface enamel microhardness.…”
Section: Discussionsupporting
confidence: 91%
“…These differences could be related to differences in specimen preparation methods, the degree of enamel mineralization, or local variations resulting from enamel rods and tufts. [ 20 ] However, there were no significant differences in the mean SMH value among the groups at Baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous reports deal with the transformation of ESW using o-phosphoric acid [2,8,10,13,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]55], but the possibility of the production of calcium hydrogen phosphate from ESW has been reported by only one scientific report [42] and one patent [56]. Laohavisuti et al [42] prepared calcium hydrogen phosphate of high purity/yield of 99.63% using ESW, which is much higher than the mass yield observed in our research (77.06 ± 6.21%), but authors used an ESW calcination at 500 • C for two hours where all organic matter was incinerated, and a much greater o-phosphoric concentration (50%) for the solvation of ESW calcium carbonate.…”
Section: Eggshell Waste Transformation Using 10% Acetic and 15% O-pho...mentioning
confidence: 99%
“…In continuation of our efforts oriented toward the complete utilization of ESW, in our present research, we have examined the possibility of chemical transformation of ESW with acetic and o-phosphoric acid to the corresponding calcium salts and eggshell membranes. Although the use of o-phosphoric and acetic acid for the production of corresponding Ca-salts from eggshell waste, such as calcium hydroxyapatite [2,8,10,13,[27][28][29][30][31][32][33][34][35][36][37][38][39], calcium triphosphate [13,28,[30][31][32]34,38,[40][41][42], calcium diphosphate [42,43] and much less studied calcium monophosphate [42] or calcium acetate [44,45], have been reported, the novelty of our research lies in the use of eggshell halves and pieces In this respect, our research group has been oriented towards the possibility of the complete utilization of eggshell waste, using the most common industrial processes, such as mixing, filtration, evaporation and drying, but with the aim of producing high-value-added products. Our most recent publication [1] has proven the possibility of ESW utilization for the production of egg white protein solution, calcium chloride dihydrate as a food-grade additive, and eggshell membranes, using ESW transformation with 5% (w/v) hydrochloric acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation